Symbolic Functions of Graffiti in Padang City of Indonesia: Critical Linguistic Landscape Studies - Yendra Yendra; Ketut Artawa; I Nyoman Suparwa; Made Sri Satyawati (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This study concerned with language in written form that is visible as graffiti in the Padang city, Indonesia landscape. The mushroomed of graffiti in Padang city landscapes increasingly has been a growing problem in society. Even local government as the official authority has created some task to prohibit graffiti, but a new graffiti has always been emerging in public space. Therefore graffiti has been considered a crime. It is interesting to explore graffiti in Padang city landscapes from other perspectives, particularly the symbolic functions of graffiti. The study uses qualitative approaches by applying Critical Discourse Analysis. The result shows that graffiti in Padang city landscapes accomplished two principal symbolic functions; first graffiti as a medium of demonstration in which providing space for marginalized expression with the opportunity to voice controversial ideas publically; second graffiti as social critics in which providing input into the public discourse that is not concerned by other conventional media.